Assessment of Physicochemical and Biological Properties and Threats on The Sorik Lake of Inderagiri River, Sumatera Indonesia - Yusni Ikhwan Siregar; Defri Yoza; Rika Kurniawan (Riau University, 2021)
Intensive agricultural practices in the upper land of the Indragiri river bring about problem to oxbow-lakes spreading out along in the middle and downstream of the river. Danau Sungai Sorik (DSL) typically included to oxbow-lake, situated in the middle part of Indragiri River, one of four big river in Riau Province, Sumatera. Since the catchment area of the lake were totally urban, accordingly the dynamic equilibrium of lake ecosystem were shifted. The lakes were reportedly degraded in terms of hydrological regime, high sedimentation, fully vegetated and low biological diversity. The local government has repeatedly normalized the depth of the lake in related to development of water attraction, restocking of invading species of fish, cage culture and rice field along the edge of the lake. The present papers aimed at characterizing and assessment of physicochemical and biological properties of the water. Further, potential threats on the sustainability of the lake were assessed. Based on chemical properties of water including BOD5, phosphate and Nitrate range were of (3.26-7.43), (0.11-0.13) and (0.229-0.433) m/L, respectively, were categorized into un-equilibrium or slightly polluted. The water transparency appeared low (25-29) cm, the pH of 6.0-6.5) and temperature of 31-32 0C. Apparently, the diversity index (H), dominancy index and similarity index of phytoplankton ranged from (0.9110-1.2211), (0.3201-0.6136) and (0.3939-0.6290, respectively. It suggested slightly dominated by certain species